KAJIAN IMPLIKASI STRUKTURAL PENGGUNAAN KOLOM PIPIH PADA BANGUNAN BETON BERTULANG BERTINGKAT RENDAH DI WILAYAH GEMPA TINGGI - I Wayan Artana; I Wayan Muka (WidyaTeknik, 2026)
The use of flat columns in low-rise reinforced concrete buildings is increasingly found in Bali, mainly due to architectural aesthetic considerations. Although beneficial for architectural layout, flat columns in high seismic regions require careful evaluation because they may affect lateral stiffness, flexural capacity, ductility, stress concentration, and plastic hinge formation. This study evaluates the effect of flat columns on the seismic response of low-rise reinforced concrete buildings using finite element-based numerical simulation. The analyzed model is a three-story reinforced concrete moment-resisting frame with column variations of 300 mm × 300 mm, 200 mm × 450 mm, 150 mm × 500 mm, and 120 mm × 600 mm. Gravity loads refer to SNI 1727:2020, while seismic response spectrum analysis refers to SNI 1726:2019 for medium soil conditions in Denpasar. Model validation was carried out by checking the fundamental period, seismic weight, and element segmentation convergence. The results show that flatter column sections produce greater stiffness imbalance between the strong and weak directions. In the 120 mm × 600 mm column model, weak-axis inter-story drift increased by approximately 31.8% compared with the 300 mm × 300 mm column model, while the capacity ratio of several ground-floor columns approached 0.94. Pushover analysis indicates that flat columns tend to accelerate plastic hinge formation in ground-floor columns along the weak direction. Therefore, flat columns in low-rise buildings located in seismic regions require aspect ratio limitation, proper column orientation, closer transverse confinement detailing, and seismic performance evaluation from the early design stage.